A real time PCR based approach for the quantitative detection of FUS-CHOP fusion transcripts in human liposarcoma - Patil, Nitin; Abba, Mohammed L.; Allgayer, Heike (Advances in medical sciences, 2012)
Purpose Histology still forms the backbone for the diagnosis of the myxoid and round cell subtypes of liposarcoma but the molecular identification of the different transcript variants remains a challenge, due, in part, to the complexity of multiple overlapping exons that they share between them. This study was conducted to develop and evaluate a more sensitive platform than existing semi-quantitative approaches for detecting FUS-CHOP transcripts. Materials and methods In the present investigation we describe a novel approach using real-time PCR to identify and differentiate the fusion transcripts formed in the t(12; 16)(q13; p11) chromosomal translocation. This method is founded on the basis of transcript individualized primers and probes, which were designed to detect specifically the different variants in both frozen and FFPE tissues. Results Our results show that the method is highly specific, sensitive, and superior to the widely used nested PCR approach, and is accurately able to differentiate the most common variants, as well as quantify copy numbers. Primer amplification and probe detection of FUS-CHOP from genomic DNA of human, mouse, cocker spaniel and chicken sources all resulted in completely negative results indicating this technique is specific for human RNA derived transcripts. Conclusion This new method offers an additional tool in the investigation of liposarcoma that may impact considerably on missed diagnosis and it's accompanying clinical ramifications.
Available online 18 March 2014
Gesehen am 28.06.2018